A Conceptual Review of the Potential of Cool Roofs as an Effective Passive Solar Technique: Elaboration of Benefits and Drawbacks - Ashtari, Babak; Yeganeh, Mansour; Bemanian, Mohammadreza; Vojdani Fakhr, Bahereh (Frontiers in Energy Research, 2021)
Cool roofs, as feasible and efficient passive solar technique that reduces building energy requirements for cooling and improves indoor thermal comfort conditions, have received considerable attention in recent years and as a result, a number of concepts, methods, and experiences have been developed during the related research. Although some studies have been conducted on this subject in the form of review articles, taking into consideration the large number of publications, there is still a call for some review papers dealing with the potential of cool roofs and providing a thorough report on their energy performance and a detailed summary of their pros and cons on the basis of the relevant studies. On this account, this study contributes a systematic review of the issued paper in Scopus and Web of Science regarding the cool roof technologies to recognize the advantages and challenges of cool roofs in practice and its future trends. In addition, detailed summary of advantages and drawbacks of this passive solar measure has been developed, as itemized factors corresponded to the codified references. A total of 90 published reports were analyzed, declaring that a cool roof is an efficient approach for generating clean energy on the building scale. This article induces an overall view of the advantages and restrictions of the cool roof throughout the world. Conclusions give a valuable reference for improving the cool roof design for their more widespread use in the building industry.